Analysis of the implementation of additional selection of village head candidates in bangkalan regency from a human rights perspective - Salim, Moh (Faculty of Law, University of Muhammadiyaha Surabaya, 2024)
This research aims to analyze the implementation of additional selection of village head candidates in Bangkalan Regency based on Bangkalan Regent Regulation No. 89/2020 from a human rights perspective. The main focus of this research is to discuss the restrictions on village head candidates stipulated in the policy, as well as its implications for the right to be elected and participate in governance at the village level. In the context of local democracy, these restrictions raise questions about the compatibility of the selection rules with human rights principles, particularly the rights to equality and non-discrimination. This research uses a normative legal research method with a statute approach, examining various relevant regulations and assessing the extent to which this policy is in line with human rights provisions at both the national and international levels. The results show that this additional selection has the potential to limit individual political rights and needs to be reconsidered within a human rights framework.